Meetei Women in the Political Sphere of Manipur. Issue 1 (June 2021) - Rojibala, Ningombam
History has its testimony to the active participation of Meetei women during social and political crises in the conflict-ridden society of Manipur. The historic events of Nupi lal (women's war) 1904 and 1939 during the British colonial period of Manipur and the nude protest by a group of Meetei women at the western gate of Kangla in 2004 are worth mentioning. Such an active engagement of Meetei women in the political sphere of society, which is considered to be the world of men, makes them appear to challenge the delineation of the two worlds—'ghar and bahir', the home and the world—delineated for women and men, respectively. While it would be facile to judge the status of Meetei women based on their ostensibly visible appearances, there is no simple answer to the question of whether they are/are not bound by the boundaries of the home and the world. This article investigates the nature of Meetei women's engagement in the political sphere to see if their actions are in strict adherence to feminist political ideologies. This article also problematizes the straitjacketing of binaries of protector/protected, victim/agent, public/private and oppressor/victim.